The Death of Distance Revisited: Cyberplace, Physical and Relational Proximities - Emmanouil Tranos; Peter Nijkamp (Tinbergen Institute, 2012)
This paper studies the impact of physical distance and different relational proximity types on the formation of the Internet infrastructure. Although there is some anecdotal evidence on the 'end of geography' effect of the Internet, the relationship between physical space and the Internet has not been yet scrutinized. In addition, owing to the network nature of the Internet, the structure of the Internet infrastructure (the cyber-place) cannot be approached in a unidimensional way. Our paper builds upon recent studies in economic geography and relational proximities, and aims to study whether physical distance survives in virtual geography even after controlling for relational proximities. In order to do so, a unique and extensive database with geo-coded IP links is utilized. Based on this, a spatial interaction model with panel data specifications is constructed to study the impact of different types of proximity on the formation of cyber-place. The above analysis is framed by a complex network analysis exercise, which enhances our understanding of the complexity of the Internet infrastructure from a spatial network perspective. Our results indicate that physical distance, but also different relational proximities, have a significant impact on the intensity of the Internet infrastructure, highlighting the spatiality of the Internet.
urn:NBN:nl:ui:31-1871/38500
Keywords: C23; H54; L96; 330; death of distance; Internet geography; Internet infrastructure; distance; proximities; spatial interaction models; Internet; Telekommunikationsnetz; Geographische Entfernung; Wirtschaftsgeographie